Pengaruh Pendekatan Teks Cerita Bahasa Arab Terhadap Peningkatan Keterampilan Maharah Kalam Pada Pembelajaran Bahasa Arab Siswa Kelas VIII di MTs Al-Khairiyah Natar - Mizan, Ahmad Nur Mizan; Mardhiyyah, Ainun; Basyar , Syarifudin (Cipta Media Harmoni, 2025)
The purpose of this study was to analyze the effect of Arabic story text method in improving maharah kalam skills in class VIII students of MTs Al-Khairiyah Natar. This study used a quantitative approach with a quasi-experiment research design, in which the experimental class (VIII A) consisting of 38 students and the control class (VIII B) consisting of 31 students became the research subjects. The instrument used was a test question that had been tested for validity and reliability. Data analysis techniques include N-gain test and hypothesis testing using Independent Sample T Test. The results showed that the average N-Gain of the experimental class was 0.62, which was categorized as a moderate improvement, while the average N-Gain of the control class was only 0.16, which was categorized as low. The results of hypothesis testing show the Sig (2-tailed) value ≤ P Value, which is 0.00 ≤ 0.05, which means that there is a significant effect of the Arabic story text method on improving maharah kalam in Arabic language learning in class VIII MTs Al-Khairiyah Natar.